Indoxyl Sulfate Affects Glial Function Increasing Oxidative Stress and Neuroinflammation in Chronic Kidney Disease: Interaction between Astrocytes and Microglia - Simona Adesso; Simona Adesso; Tim Magnus; Salvatore Cuzzocrea; Michela Campolo; Björn Rissiek; Orlando Paciello; Giuseppina Autore; Aldo Pinto; Stefania Marzocco (Frontiers Media S.A., 2017)
Indoxyl sulfate (IS) is a protein-bound uremic toxin resulting from the metabolism of dietary tryptophan which accumulates in patients with impaired renal function, such as chronic kidney disease (CKD). IS is a well-known nephrovascular toxin but little is known about its effects on central nervous system (CNS) cells. Considering the growing interest in the field of CNS comorbidities in CKD, we studied the effect of IS on CNS cells. IS (15-60 μM) treatment in C6 astrocyte cells increased reactive oxygen species release and decreased nuclear factor (erythroid-derived 2)-like 2 (Nrf2) activation, and heme oxygenase-1 (HO-1) and NAD(P)H dehydrogenase quinone 1 expression. Moreover, IS increased Aryl hydrocarbon Receptor (AhR) and Nuclear Factor-kB (NF-kB) activation in these cells. Similiar observations were made in primary mouse astrocytes and mixed glial cells. Inducible nitric oxide synthase and cyclooxygenase-2 (COX-2) expression, tumor necrosis factor-α and interleukin-6 release and nitrotyrosine formation were increased by IS (15-60 μM) in primary mouse astrocytes and mixed glial cells. IS increased AhR and NF-kB nuclear translocation and reduced Nrf2 translocation and HO-1 expression in primary glial cells. In addition, IS induced cell death in neurons in a dose dependent fashion. Injection of IS (800 mg/kg, i.p.) into mice induced histological changes and increased COX-2 expression and nitrotyrosine formation in thebrain tissue. Taken together, our results show a significant contribution of IS in generating a neurotoxic enviroment and it could also have a potential role in neurodegeneration. IS could be considered also a potential therapeutical target for CKD-associated neurodegenerative complications.